High sodium intake and fluid overhydration predict cardiac structural and functional impairments in chronic kidney disease - Duan, Suyan; Ma, Yuchen; Lu, Fang; Zhang, Chengning; Guo, Honglei; Zeng, Ming; Sun, Bin; Yuan, Yanggang; Xing, Changying; Mao, Huijuan; Zhang, Bo (Frontiers in Nutrition, 2024)
Background: High sodium intake and fluid overhydration are common factors of and strongly associated with adverse outcomes in chronic kidney disease (CKD) patients. Yet, their effects on cardiac dysfunction remain unclear.The study aimed to explore the impact of salt and volume overload on cardiac alterations in non-dialysis CKD.Methods:In all,409 patients with CKD stages 1-4 (G1-G4) were enrolled. Daily salt intake (DSI) was estimated by 24-h urinary sodium excretion. Volume status was evaluated by the ratio of extracellular water (ECW) to total body water (TBW) measured by body composition monitor. Recruited patients were categorized into four groups according to DSI (6 g/day) and median ECW/TBW (0.439). Echocardiographic and body composition parameters and clinical indicators were compared. Associations between echocardiographic findings and basic characteristics were performed by Spearman's correlations. Univariate and multivariate binary logistic regression analysis were used to determine the associations between DSI and ECW/TBW in the study groups and the incidence of left ventricular hypertrophy (LVH) and elevated left ventricular filling pressure (ELVFP). In addition, the subgroup effects of DSI and ECW/TBW on cardiac abnormalities were estimated using Cox regression.Of the enrolled patients with CKD, the median urinary protein was 0.94 (0.28-3.14) g/d and estimated glomerular filtration rate (eGFR) was 92.05 (IQR: 64.52-110.99) mL/min/1.73 m2. The distributions of CKD stages G1-G4 in the four groups was significantly different (P=0.020). Furthermore, compared to group 1 (low DSI and low ECW/TBW), group 4 (high DSI and high ECW/TBW) showed a 2.396-fold (95%CI: 1.171-4.902; P=0.017) excess risk of LVH and/or ELVFP incidence after adjusting for important CKD and cardiovascular disease risk factors. Moreover, combined with eGFR, DSI and ECW/TBW could identify patients with higher cardiac dysfunction risk estimates with an AUC of 0.704 (sensitivity: 75.2%, specificity: 61.0%). The specificity increased to 85.7% in those with nephrotic proteinuria (AUC=0.713). The magnitude of these associations was consistent across subgroups analyses.The combination of high DSI (>6 g/d) and high ECW/TBW (>0.439) independently predicted a greater risk of LVH or ELVFP incidence in non-dialysis CKD patients. Moreover, the inclusion of eGFR and proteinuria improved the risk stratification ability of DSI and ECW/TBW in cardiac impairments in CKD.